Efeito da intervenção terapêutica ocupacional junto a crianças com déficts de percepção visual, coordenação motora e integração visuo-motora - Araújo, Rita de Cássia Tibério [UNESP]; Zafani, Mariana Dutra [UNESP]; Pereira, Débora Morais [UNESP] (My University, 2012)
To students with special educational needs participate actively at school are required effective and systematic investment, involving the school community as a whole. The occupational therapist is one of the professionals who can facilitate this student inclusion process. This study aimed to discuss the occupational therapy intervention effects with two disability children with deficits in visual perceptual skills, motor coordination and visual motor integration, that was included in regular education. The Beery-Buktenica Developmental Test of Visual Motor Integration was use to evaluate visual perceptual skills, motor coordination and visual-motor integration. Because the deficits presented in the functions investigates was identified the need of an occupational therapy intervention program designed to improve the performance in theses functions. After the program, the test was reapplied. The results pointed to an improvement of all functions considered deficient. These results highlight to the training importance to improve the performance in abilities evaluated.

Para que o aluno com necessidades educacionais especiais participe ativamente da escola são necessários investimentos efetivos e sistemáticos, envolvendo a comunidade escolar como um todo. O terapeuta ocupacional é um dos profissionais que pode favorecer o processo de inclusão destes alunos. Este estudo teve como objetivo discutir o efeito da intervenção terapêutica ocupacional junto a duas crianças com deficiência incluídas no ensino regular, com déficits de percepção visual, coordenação motora e integração visuo-motora. Para a avaliação das habilidades de percepção visual, coordenação motora e integração visuo-motora foi utilizado o Beery-Buktenica Developmental Test of Visual-Motor Integration. Em virtude dos déficits apresentados nas funções investigadas foi verificada a necessidade de aplicação de um programa de intervenção terapêutico ocupacional visando à melhora dessas funções. Após aplicação do programa, o teste foi reaplicado. Os resultados apontaram para a melhora de todas as funções consideradas deficitárias, sinalizando a importância do treinamento de desempenho.
Occupational therapy intervention effect for children with deficits in visual perception, motor coordination and visual- motor integration
Keywords: Terapia Ocupacional; Educação Especial; integração visomotora